Hubungan Indonesia dan Australia dalam Perspektif Hubungan Islam dan Barat: Benturan Peradaban atau Kerjasama? - Damayanti, Rizki (Andalas Journal of International Studies (AJIS), 2023)
Among the relations between two countries which are seen as representing the relationship between Islam and the West is the relationship between Indonesia and Australia, where the relationship between these two close neighboring countries is often clashed with perceptions of the relationship between Islam and the West. In this case, Huntington's thesis, states the Clash of Civilizations, is often still the basis for strengthening the view of many parties that Islamic and Western civilization will never meet in harmony. Contrary to Huntington's thesis, Bassam Tibi put forward an argument regarding the Inter-Civilizational Dialogue which allows opportunities for cooperation between Islam and the West. This article is library research using qualitative methods. Data collection techniques were carried out through document review and literature study. This article finds that Indonesia-Australia relations have complex dynamics, where clashes of civilizations, the phenomenon of Islamophobia, as well as civilizational dialogue, or even cooperation are possible in the course of Indonesia's relations with Australia.